Measurements and Stochastic FEA with Application in Thermomechanical Characterization of Electronic Packages - Bendaou, Omar; Bendaou, Othmane; Bourzeix, François; Agouzoul, Mohamed; El Hami, Abdelkhalak (Journal of Engineering and Technological Sciences, 2016)
The aim of this study was to validate/calibrate two tools to be able to reliably measure/predict warpage at ambient temperature, especially for ball grid array (BGA) electronic packages. The tools used in this study were a high-precision microscope and a finite-element model. First, the authors calibrated the microscope by comparing the obtained results with the results obtained with a shadow moiré machine (considered as reference) and then the finite-element model was calibrated to the microscope. The numerical study was not restricted to a deterministic approach; a stochastic study was also performed for taking into account parameter uncertainties. The results demonstrated that both tools are reliable alternatives for thermomechanical characterization of BGA packages at room temperature. The results obtained in the finite-element model calibration phase showed the importance of adopting a probabilistic approach, at the same time proving that the elaborated warpage numerical model is a good basis for future advanced analysis such as optimization or numerical design of experiments while having reasonable investment and time-consumption costs.